Teaching behavior analysts to create multiple baseline graphs using SigmaPlot. (8th October 2021) - Cihon, Joseph H.; Ferguson, Julia L.; Milne, Christine M.; Leaf, Justin B.
Abstract: The development and visual inspection of graphical representations of single subject designs is a hallmark of applied behavior analysis. Much of the research on training individuals to develop single subject design graphs has involved a limited number of graphing programs (i.e., Microsoft Excel and Prism). Many graphing programs require task analyses specific to their user environment (e.g., separating data from different conditions in different columns), which may decrease the likelihood of generalization of the results of previous studies to other graphing programs (e.g., SigmaPlot). In the present study, we have evaluated the effectiveness of a video tutorial for training behavior analysts to create multiple baseline across participants graphs using SigmaPlot, which includes the inputting of data. The effectiveness of the video tutorial was evaluated using a multiple baseline design. For two of the participants, the video tutorial alone resulted in mastery level performance. The third participant required feedback before reaching mastery level performance. All three participants demonstrated generalization to a different data set and performance maintained following a week of no intervention. Social validity data indicates that participants found the skill, training, and results to be important, enjoyable, and acceptable.